PENGARUH RASIO PROFITABILITAS TERHADAP NILAI PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - DEWI OKTARY; MULIANI MULIANI (STIE 'INDONESIA' Pontianak, 2020)
This study aims to influence the ratio of profitability to the value of consumer goods sector companies listed on the Indonesia Stock Exchange in 2015-2017. Sampling in this study uses purposive sampling with the criteria of companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2015 -2017, having 28 company. This research method is a quantitative method with data analysis techniques using multiple linear regression analysis. The results of this study are the variable ROA does not have a significant effect on company value, it can be seen the value of t count 0.783 < t table 1.966 and significant 0.436 > 0.05. ROE has a significant positive effect on firm value. It can be seen t count ROE 2.983> t table value 1.9666 and significant 0.005 < 0.05. Whereas the NPM variable does not have a significant effect on the value of the company. Can be seen fro m the variable t value 0.281 <t table 1.9966 with a significant 0.780> 0.05. Simultaneously ROA, ROE and NPM have a significant influence on the value of the company. This can be seen from the F test obtained F count of 34.487> F table 2.74 significant level of 0.000 < 0.05 simultaneously significant effect on firm value.